Correlations among PPAR𝜸, DNMT1, and DNMT3B Expression Levels and Pancreatic Cancer - Valerio Pazienza; Francesca Tavano; Giorgia Benegiamo; Manlio Vinciguerra; Francesca Paola Burbaci; Massimiliano Copetti; Fabio Francesco di Mola; Angelo Andriulli; Pierluigi di Sebastiano (PPAR Research)
Emerging evidence indicates that peroxisome proliferator-activated receptor γ (PPARγ) and DNA methyltransferases (DNMTs) play a role in carcinogenesis. In this study we aimed to evaluate the expression of PPARγ, DNMT1, and DNMT3B and their correlation with clinical-pathological features in patients with pancreatic cancer (PC), and to define the effect of PPARγ activation on DNMTs expression in PC cell lines. qRT-PCR analysis showed that DNMT3B expression was downregulated in tumors compared to normal tissues (𝑃=0.03), whereas PPARγ and DNMT1 levels did not show significant alterations in PC patients. Expression levels between PPARγ and DNMT1 and between DNMT1 and DNMT3B were highly correlated (𝑃=0.008 and 𝑃=0.05 resp.). DNMT3B overexpression in tumor tissue was positively correlated with both lymph nodes spreading (𝑃=0.046) and resection margin status (𝑃=0.04), and a borderline association with perineural invasion (𝑃=0.06) was found. Furthermore, high levels of DNMT3B expression were significantly associated with a lower mortality in the whole population (HR=0.485; 95%CI=0.262–0.895, 𝑃=0.02) and in the subgroup of patients without perineural invasion (HR=0.314; 95%CI=0.130–0.758; 𝑃=0.01), while such association was not observed in patients with tumor invasion into perineural structures (𝑃=0.70). In conclusion, in vitro and in vivo PPARγ and DNMTs appear interrelated in PC, and this interaction might influence cell phenotype and disease behavior.